Emotional Arousal and its Correlative with an Enzyme (LDH) and the Performance of some Offensive Skills Compound for Female Students in Basketball - Hasan Saleh Mahdi Al-Okbi (Journal of Global Pharma Technology, 2018)
The importance of the research is that its results may reveal the development of motor abilities and support learning the offensive skills of basketball in the first stage students through the use of more than one method in the educational unit, as well as determining the importance of research in the need to study and research in the development and teaching of offensive skills basketball Because the game has a variety of skills, and the study aimed to identify the relationship between emotional arousal and enzyme (LDH) through some variables related to basketball students. Laboratory tests were conducted on a sample of 34 female students from the Faculty of Physical Education and Sports Science for Girls at the University of Kufa. After obtaining the results, they were treated statistically and presented in tables. The results were reached, which is the high level of emotional arousal in individuals the study sample is the result of their psychological effect. Decreased enzyme activity (LDH) due to high level of emotional arousal was inversely associated with the resulting slow work and sending of instructions. Low performance of basketball offensive skills due to high level of emotional arousal.Keywords: Emotional arousal, Enzyme (LDH), Compound offensive skills and basketball.